The use of carbon fiber/epoxy braided composites in the design of a rowing shell - Cui, C.; Lepp, E.; Ead, A. S.; Carey, J. (University of Alberta, Department of Mechanical Engineering, 2020)
Fiber-reinforced composites are used for a variety of different sports equipment one ofwhich is the outer layer of a rowing shell. After comparing the properties of Carbon Fiber towhat is typically used to manufacture rowing shells (Kevlar and Fiberglass), it was evident thatCarbon Fiber was a more optimal material to manufacture a rowing shell due to its high elasticmodulus. To maximize the longitudinal elastic modulus while increasing the transverse elasticmodulus, a braid angle of 20 degrees was determined to be best. Although this decreases thelongitudinal elastic modulus from 135 GPa to 36.6 GPa, it is still comparable to the longitudinalelastic modulus of the commonly used fiberglass. It also increases other factors such as thetransverse elastic modulus and the torsional strength. This subsequently increases the overallstiffness of the shell, such that the shell will be more durable when facing unexpected forces thatmay occur on the water. While carbon fiber is more expensive than typical fibers, the quality ismuch higher and it is more durable and lightweight, which allows for decreased drag. Ultimately,using 2D Braided Carbon Fiber/Epoxy Composite to manufacture a rowing shell will result in amore efficient boat that will have a longer lifespan. This study will examine the use of carbon fiber braided composites in arowing shell in comparison to unidirectional Kevlar and Fiberglass composite parts.